Analisis Kebutuhan Pengembangan Media Papan Pintar Hijaiyah (PAPINJAI) dalam Pengenalan Huruf Hijaiyah Anak Usia 3-4 Tahun - Lala Lajimah; Taopik Rahman; Anggi Maulana Rizqi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Introducing Hijaiyah letters during early childhood is fundamental for developing Qur'anic literacy and strengthening children's religious values. However, existing studies have predominantly evaluated the effectiveness of learning media, while limited attention has been given to identifying teachers' needs as the basis for developing media that aligns with the developmental characteristics of children aged 3–4 years. This study aimed to analyze the needs for developing the Hijaiyah Smart Board (PAPINJAI) as an interactive learning medium. A descriptive qualitative approach employing needs analysis was conducted with three Class A teachers from three Early Childhood Education (ECE) institutions. Data were collected through observations, semi-structured interviews, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings revealed that Hijaiyah learning was still dominated by lectures, question-and-answer sessions, repetition, and conventional media such as letter cards, posters, whiteboards, and Iqra' books, resulting in children's limited attention, motivation, and active participation. All participating teachers consistently emphasized the need for colorful, manipulative, play-based, and interactive media that enable children to touch, arrange, and move Hijaiyah letters directly. The novelty of this study lies in providing an empirical needs-analysis framework as the foundation for developing PAPINJAI, a learning medium specifically designed according to the developmental characteristics of children aged 3–4 years. This study contributes scientifically by generating evidence-based design requirements for early childhood Islamic learning media and provides practical implications for developing more engaging, developmentally appropriate, and child-centered learning media in ECE settings